Erythromycin resistance in Streptococcus pyogenes in Italy. - Bassetti, M (Centers for Disease Control and Prevention, 2000)
In a prospective study of acute pharyngitis in Italian children, 69 (38.3%) of 180 isolates of Streptococcus pyogenes were resistant to macrolides. S. pyogenes was eradicated in 12 (63.1%) of 19 patients with erythromycin-resistant S. pyogenes treated with clarithromycin and in 22 (88%) of 25 patients with erythromycin-susceptible strains. The constitutive-resistant phenotype was correlated with failure of macrolide treatment.